Genetics’ Influence on Drug Abuse & Addiction; Interactions of Endophenotypes & Genotypes - Behnam Zamanian; Ali Goodarzi; Hamed Ekhtiari (Basic and Clinical Neuroscience, 2010)
A B S T R A C T “Addiction” is a multifaceted complicated disorder with many interrelated causes, as well as environmental and genetic features. Several hereditary variables that have an effect on these features might work in together to influence vulnerability and the extent of being an addict. Molecular re-sequencing of the latest and formerly researched genes holds a crucial place with regards to the breakthrough of hereditary alternates of possible interest. This report presents a brief review of this complicated disorder through genotyping and phenotyping aspects, and examines their correlation in creating and driving this disease.